Integrasi Islam dan Sains Model Tasawuf - Ngadiman; Kholid Mawardi (Publikasi Indonesia, 2022)
This study is intended to examine the integration of Islam and science with the Sufi model. The Sufi tradition contains a large number of cosmological and metaphysical doctrines explained by a Sufi master and an Irfani expert. Sufism includes methods of spiritual perception that deal with almost all different psychic faculties on action, love, and intellectual levels. The study method used is qualitative with library research. Religion and science cannot be separated from the point of view of Sufism, there are many things that can be used as lessons from science, even more so from Sufism. The science of Sufism is no longer an era that is always denied and debated. Therefore, it is time for us to take what is good in Sufism and discard what is not in accordance with sharia. On the other hand, let the Sufis continue to improve ukhuwah Islamiyah and be open (inclusive), and not closed (exclusive) as if the truth only belongs to them.